2007
DOI: 10.1111/j.1601-0825.2007.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

PTCH germline mutations in Chinese nevoid basal cell carcinoma syndrome patients

Abstract: The frequent germline PTCH mutations detected in our series provide further evidence for the crucial role of PTCH in the pathogenesis of nevoid basal cell carcinoma syndrome in Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Of the six mutations identified, five (c. 403C>T, c.1012C>T, c.2179delT, c.2824delC, c.3162dupG) resulted in truncation of the PTCH protein. These results were in consistent with the previous reports that most PTCH mutations lead to a premature termination of the protein (Li et al, 2008;Wicking et al, 1997) .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Of the six mutations identified, five (c. 403C>T, c.1012C>T, c.2179delT, c.2824delC, c.3162dupG) resulted in truncation of the PTCH protein. These results were in consistent with the previous reports that most PTCH mutations lead to a premature termination of the protein (Li et al, 2008;Wicking et al, 1997) .…”
Section: Discussionsupporting
confidence: 83%
“…So far, several studies have provided evidence that PTCH might take part in the pathogenesis of NBCCS-associated and sporadic KCOTs (Barreto et al, 2000;Gu et al, 2006;Sun et al, 2008). In this study, we identified 6 additional PTCH mutations in 2 out of 8 sporadic and 3 out of 4 NBCCS-associated KCOTs, consisted of 2 nonsense, 3 frameshift and 1 inframe duplication mutations.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, the original references on mutations were all on syndromic patients and the 6 WHO references on non-syndromic cases included syndromic patients. There were numerous subsequent papers dealing with PTCH mutations in syndromic and nonsyndromic OKCs, which have shown mutations in approximately 85 % of syndromic cases and 30 % of non-syndromic cases [26][27][28][29][30][31][32].…”
Section: The Cyst/neoplasm Interfacementioning
confidence: 99%